1996
DOI: 10.1093/infdis/174.5.920
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus (HBV)/Hepatitis D Virus (HDV) Coinfection in Outbreaks of Acute Hepatitis in the Peruvian Amazon Basin: The Roles of HDV Genotype III and HBV Genotype F

Abstract: Recurring outbreaks of acute hepatitis have been a significant cause of morbidity and mortality among Peruvian military personnel stationed in the Amazon Basin region of Peru. The role of hepatitis B virus (HBV) and hepatitis D virus (HDV) infection was investigated as the possible cause of acute hepatitis among 88 military patients stationed at four different jungle outposts during 1992-1993. Analysis of serum markers indicated that 95% (84/88) had evidence of acute HBV infection; 64% (54/84) were also infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
146
1
13

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(175 citation statements)
references
References 18 publications
12
146
1
13
Order By: Relevance
“…Moreover, HDV infection in HBV carriers has been associated with an un- (Soares et al 1994, Casey et al 1996. The impact of HDV infection should be taken into consideration in the communities that were evaluated in this study, due to the very high prevalence found for this virus.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, HDV infection in HBV carriers has been associated with an un- (Soares et al 1994, Casey et al 1996. The impact of HDV infection should be taken into consideration in the communities that were evaluated in this study, due to the very high prevalence found for this virus.…”
Section: Discussionmentioning
confidence: 94%
“…Recentemente, novos estudos implicam o genótipo III do VHD associado ao subtipo F do VHB, como responsáveis por formas graves de hepatite que acometeram militares peruanos na bacia amazônica peruana 8 .…”
Section: Patogêneseunclassified
“…O HDV-RNA persistentemente positivo no soro no estágio agudo de infecção, indica a progressão para a cronicidade em 30 . Através de técnicas de análise genética de PCR-amplificado do genoma VHD, diretamente clonado e seqüenciado 7 , o diagnóstico laboratorial da infecção pelo vírus D, apesar da complexidade deste método e de não ser utilizado na rotina, tornou-se mais preciso, principalmente no que tange ao conhecimento da gravidade da infecção e de seu prognóstico 8 .…”
Section: Diagnóstico Laboratorialunclassified
“…Due to the importance of genotype F in the New World, a method capable of discriminating it should be useful for HBV molecular epidemiology studies in the Americas. Recently, it was shown that the presence of a SmaI restriction site could be used to recognize sequences from genotype F (19). Our method presents the advantage that is very simple and fast.…”
mentioning
confidence: 99%